Influences on the implementation of Mini-CEX and DOPS for postgraduate medical trainees' learning: A grounded theory study. (3rd April 2019) - Lörwald, Andrea C.; Lahner, Felicitas-Maria; Mooser, Bettina; Perrig, Martin; Widmer, Matthias K.; Greif, Robert; Huwendiek, Sören
Abstract: Introduction: In order for Mini-Clinical Evaluation Exercise (Mini-CEX) and Direct Observation of Procedural Skills (DOPS) to actually have a positive effect on trainees' learning, the way in which the tools are implemented is of key importance. However, there are many factors influencing their implementation. In this study, we aim to develop a comprehensive model of such factors. Methods: Using a constructivist grounded theory approach, we performed eight focus groups. Participants were postgraduate trainees and supervisors from three different specialties; all were experienced with Mini-CEX and/or DOPS. Data were analyzed for recurring themes, underlying concepts and their interactions using constant comparison. Results: We developed a model demonstrating how the implementation of Mini-CEX and DOPS for trainees' learning is influenced by 13 factors relating to four categories: organizational culture (e.g. value of teaching and feedback), work structure (e.g. time for Mini-CEX and DOPS, faculty development), instruments (e.g. content of assessment), and users (e.g. relationship between trainees and supervisors), and their interaction. Conclusions: We developed a complex model of influencing factors relating to four categories. Consideration of this model might support successful implementation and trainees' learning with Mini-CEX and DOPS.